The Role Of Organizational Commitment In Mediating The Influence Of Transformational Leadership And Organizational Culture On Employee Performance - Mokhamad Sholihin; Endang Suswati; Navi Muda Priyatna (International Journal Labs, 2024)
This study aims to examine and analyze the influence of: 1) transformational leadership on organizational commitment, 2) organizational culture on organizational commitment, 3) transformational leadership on performance, 4) organizational culture on performance, 5) organizational commitment on performance, 6) transformational leadership on employee performance through organizational commitment, 7) organizational culture on employee performance through organizational commitment. This research uses an explanatory research approach, conducted at the SATPOL PP office of Mojokerto Regency. The population amounted to 59 civil servants, then sampled by census techniques. Primary data related to research variables were obtained through questionnaires given directly to respondents. Once the data is collected, it is further analyzed using path analysis. However, previously tests were carried out on validity, reliability and classical assumptions. To test the hypothesis, a t-test with an alpa of 5% is used, and to determine the organizational commitment to act as a mediator, the Sobel test with an alpa of 5% is used. The results of this study prove that: 1) transformational leadership has a significant effect on organizational commitment; 2) organizational culture has a significant effect on organizational commitment; 3) transformational leadership has no effect on employee performance; 4) organizational culture has a significant effect on performance; 5) organizational commitment has no effect on employee performance; 6) organizational commitment does not play a role in mediating the influence of transformational leadership on performance; 7) Organizational commitment plays a role in mediating the influence of organizational culture on performance.